2023
DOI: 10.2196/38096
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Information Needs Related to a Monitoring Implant for Heart Failure: Co-designed Study Based on Affect Stories

Abstract: Background RealWorld4Clinic is a European consortium that is currently developing an implantable monitoring device for acute heart failure prevention. Objective This study aimed to identify the main issues and information needs related to this new cardiac implant from the patients’ perspective. Methods A total of 3 patient collaborators were recruited to help us design the study. During 4 remotely held meeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
(61 reference statements)
0
3
0
Order By: Relevance
“… 40 The results from this study and others highlight the importance of key device features for patients. 39 , 41 44 Attention must be given to studies such as ours, given the goal of improving quality of life for the device end user. A greater understanding and adoption of patient-centric design by the dialysis community will allow more efficient product development in an industry increasingly under the pressure of narrowing margins.…”
Section: Discussionmentioning
confidence: 99%
“… 40 The results from this study and others highlight the importance of key device features for patients. 39 , 41 44 Attention must be given to studies such as ours, given the goal of improving quality of life for the device end user. A greater understanding and adoption of patient-centric design by the dialysis community will allow more efficient product development in an industry increasingly under the pressure of narrowing margins.…”
Section: Discussionmentioning
confidence: 99%
“…The aim was to gather the perspectives of a wider and more diverse panel of patients, by broadening our call for participation. More details on this part of the study (including participant quotes) can be found in Davat and Martin-Juchat (2023).…”
Section: Qualitative Research To Broaden the Perspectives Of The Studymentioning
confidence: 99%
“…We reminded them the context and objectives of the project. Then, we presented the results of our research, hypothesis by hypothesis, as detailed in Davat and Martin-Juchat (2023).…”
Section: Qualitative Research To Broaden the Perspectives Of The Studymentioning
confidence: 99%